Didactic, technological and communicational considerations for EVEA design - Santamaría-Muñoz, Jorge (2025)
In this research we determined the didactic, pedagogical, technological aspects as well as the learning methodologies which should be considered in order to develop an VTLE that guarantees a quality learning. For this purpose, we used the qualitative approach supported by the design of the grounded theory with the purpose of generating theories, concepts or hypotheses from the analysis of the interviewees' points of view and the contrast with the literature previously analyzed. In this sense, we interviewed 8 experts in the subject of design and implementation of VTLE and the data obtained were analyzed by means of the software ATLAS.TI 8, following the model of the emergent conception. According to the results obtained, we determined that in order to design a VTLE the instructional design ADDIE should be used, the resources of the VTLE should be varied to assist the diversity of learning styles and the contents should be up-to-date, the activities should be focused to solve problems of the professional context of the students and they should promote the autonomous and collaborative learning, the andragogical foundations of the students must be also considered, and finally the use of the B-Learning approach and the Flipped Classroom methodology so that they use ICT tools to support the teaching and learning processes.